Gene coevolution and regulation lock cyclic plant defence peptides to their targets. Issue 2 (15th December 2015) - Gilding, Edward K.; Jackson, Mark A.; Poth, Aaron G.; Henriques, Sónia Troeira; Prentis, Peter J.; Mahatmanto, Tunjung; Craik, David J.
Summary: Plants have evolved many strategies to protect themselves from attack, including peptide toxins that are ribosomally synthesized and thus adaptable directly by genetic polymorphisms. Certain toxins in Clitoria ternatea (butterfly pea) are cyclic cystine‐knot peptides of c . 30 residues, called cyclotides, which have co‐opted the plant's albumin‐1 gene family for their production. How butterfly pea albumin‐1 genes were commandeered and how these cyclotides are utilized in defence remain unclear. The role of cyclotides in host plant ecology and biotechnological applications requires exploration. We characterized the sequence diversity and expression dynamics of precursor and processing proteins implicated in butterfly pea cyclotide biosynthesis by expression profiling through RNA‐sequencing (RNA‐seq). Peptide‐enriched extracts from various organs were tested for activity against insect‐like membranes and the model nematode Caenorhabditis elegans . We found that the evolution and deployment of cyclotides involved their diversification to exhibit different chemical properties and expression between organs facing different defensive challenges. Cyclotide‐enriched fractions from soil‐contacting organs were effective at killing nematodes, whereas similar enriched fractions from aerial organs contained cyclotides that exhibited stronger interactions with insect‐like membrane lipids. Cyclotides are employed as versatile and combinatorial mediators of defence in C. ternatea and have specialized to affect different classes of attacking organisms.